Métropole-frontières. Lille-Kortrijk-Tournai. Faire projet en interterritorialité - Grosjean, Bénédicte; Jodogne, Simon (Autrement, 2023)
Aus den Verlagsangaben: „Comment fonctionne un espace transfrontalier? Fruit d’une trentaine d’années de coopération entre cinq intercommunalités appartenant à trois régions, l’eurométropole franco-belge Lille-Kortrijk-Tournai est un terrain d’observation privilégié. Cet ouvrage retrace comment, en l'absence de cadre commun, l'action transfrontalière arrive à « faire projet », tant au regard des finalités que des moyens déployés pour les concrétiser. Dans un contexte de fortes disparités, de transitions et de nécessaires adaptations au dérèglement climatique, il permet de penser plus globalement l'interterritorialité.“
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2024/10/26/file_9/9604308.pdf
Keywords: Departement Nord; Eurométropole Lille-Kortrijk-Tournai; Grenzüberschreitende Kooperation; Hennegau; Kortrijk; Lille; Tournai; Westflandern

L'Eurométropole Lille-Kortrijk-Tournai. Instrument au service de l'institutionnalisation de la coopération transfrontalière - Delecosse, Éric; Delhuvenne, Loïc; Leloup, Fabienne (CRISP, 2022)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2022/09/26/file_4/9260997.pdf
Keywords: Departement Nord; Eurométropole Lille-Kortrijk-Tournai; Frankreich; Grenzüberschreitende Kooperation; Hennegau; Kortrijk; Lille; Tournai; Westflandern

Study on providing public transport in cross-border regions. Mapping of existing services and legal obstacles. Rail link Lille (France) - Tournai (Belgium). Case study report - Europäische Kommission, Generaldirektion Regionalpolitik und Stadtentwicklung (Publications Office of the European Union, 2022)
This case study report presents the business model for the cross-border rail service between Lille (France) and Tournai (Belgium). This report is part of a series of 31 case studies developed in the framework of the study ‘Providing public transport in cross-border regions – Mapping of existing services and legal obstacles’. Spatial Foresight in cooperation with TCP international, TRT trasporti e territorio and EureConsult completed this study for the European Commission’s DG REGIO. The case studies highlight a variety of business models for cross-border public transport services. This includes governance arrangements and operational provisions to develop the service and address demand in border regions. These aspects will be introduced in section 2, as well as the territorial scope of the service. Section 3 presents key obstacles related to the business model as well as solutions. Section 4 is about lessons learnt from this case. This case study illustrates how the EGTC Eurometropolis Lille-Kortrijk-Tournai contributes, as a cross-border entity, to improving services for the rail connection Lille – Tournai, and encouraging key stakeholders to consider their role to offering services for the cross-border region. The Lille – Tournai connection is part of a network of cross-border public transport services contributing to further integration of the region across national, regional and language borders. The Eurometropolis facilitates governance processes and aims to develop an ecosystem of sustainable transport in which public transport plays an important role. In doing so, the Eurometropolis often has to initiate and adopt practical solutions. This case study is based on desk research including sources from French and Belgian sides of the border as well as studies covering the cross-border region. One interview was conducted with a representative from the Eurometropolis Lille-Kortrijk-Tournai, responsible for the working group “mobility, employment and local services”. The interviewee provided insights on the rail connection and its function in the cross-border region and its public transport connection from a cross-border point of view.
Keywords: Eisenbahn; Eisenbahnlinie; Eisenbahnverkehr; Eurométropole Lille-Kortrijk-Tournai; Öffentlicher Personennahverkehr

Métropole européenne de Lille (MEL). Construire une politique de l’emploi dans un cadre transfrontalier - Cassette, Bruno; Jodogne, Simon; Vaillant, David (Annales des Mines - Réalités industrielles, 2020)
Abstract: „La Métropole européenne de Lille (MEL) est confrontée à un chômage structurel avec des taux élevés, notamment dans le versant nord-est de son territoire (Roubaix-Tourcoing), à proximité de la frontière franco-belge. La MEL a, dès le début des années 2000, pris l’initiative de développer des politiques en faveur de l’emploi par des actions économiques, sociales et d’aménagement de son territoire. Frontalière de la Belgique, en particulier de la Flandre belge, qui connaît une situation de plein emploi, la MEL a souhaité, en 2018, aller plus loin, en cherchant à mieux comprendre les caractéristiques socio-économiques, les modes de fonctionnement du système flamand et ses performances pour renforcer ses politiques métropolitaines en faveur de l’emploi. Cette stratégie métropolitaine complète et s’insère dans un ensemble de dispositifs et d’actions transfrontalières visant à décloisonner le marché de l’emploi et à développer une Eurométropole Lille-Kortrijk-Tournai, de manière plus intégrée.“
Keywords: Arbeiterbewegung; Arbeitsmarkt; Eurométropole Lille-Kortrijk-Tournai; Grenzarbeitnehmer; Grenzgebiet; Grenzüberschreitende Kooperation; Lille; Roubaix; Tourcoing

Eurometropolis Lille-Kortrijk-Tournai. Cross-border integration with or without the border? - Durand, Frédéric; Perrin, Thomas (European Urban and Regional Studies, 2018)
Keywords: Departement Nord; Eurométropole Lille-Kortrijk-Tournai; Grenzüberschreitende Kooperation; Hennegau; Kortrijk; Lille; Tournai; Westflandern

The residential and symbolic dimensions of cross-border mobility. Looking at members of the French middle class in the agglomeration of Lille - Clément, Garance (European Borderlands. Living with Barriers and Bridges, 2017)
Keywords: Grenzarbeitnehmer; Lille; Mobilität; Sozialraum; Wohnungsmarkt

Halluin. Une borne à la frontière d’un territoire démembré en 1779 - Lantoine, Jennifer; Notte, Ludovic (Revue du Nord, 2013)
Abstract: „En novembre 2012, une borne de grès (d’Ostrevant ?), figurée de l’aigle impérial autrichien et de fleurs de lys et opposées, a été découverte en diagnostic sur la commune de Neuville-en-Ferrain (Nord). Basculée, à une date inconnue, dans un fossé, son emplacement primitif, à quelques décimètres de là, marquait la frontière définie par la Convention des limites de 1779 puis définitivement confirmée par la Convention de Courtrai du 28 mars 1820. Les liasses de correspondance du fonds de l’Intendance (aux archives départementales du Nord) permettent de suivre dans le détail, le long et tortueux processus de délimitation et d’abornement préalable, par réduction des enclaves héritées du Moyen Âge, à l’établissement de la première véritable frontière linéaire. La borne d’Halluin est précisément issue d’un lot de 114 pièces produites en 1780-1781 à Lille au faubourg de La Barre dans l’atelier du maître-paveur François Brasme. L’inventaire, sinon le sauvetage, de ces petits monuments, disposés à l’endroit des seuls territoires démembrés, est à entreprendre. Le statut juridique de ces bornes, considérées ici comme mobilier archéologique, mériterait aussi d’être précisé car il apparaît qu’elles marqu[ai]ent une frontière au tracé confirmé ; seraient-elles toujours significatives et immobilisées?“
Keywords: Grenzstein; Lille; Österreichische Niederlande

Mise en évidence d'une marche culturelle par le matériel figulin au Haut-Empire romain dans le Nord de la Gaule Belgique. La vallée de la Deûle - Herbin, Patrice; Loridant, Frédéric (Revue du Nord, 2003)
Abstract: „After the conquest, the influence of the Roman world varies according to the regions. The Deûle valley is situated in Gallia Belgica, at the confines of the cities of the Atrebates and of the Menapians. Potery kitchenware, fundamental implements of the household, artefact found in large amounts during archaeological excavations and above all a well-studied material reveals an area where « Gallo-Roman » potery is intimately mixed with native potery. Thus, for the Menapians, the eartheware keeps its native character (moulded potery) while among the Atrebates, the Morins and the Nervians, the inventories are altered in depth (potery shaped on the fast wheel) at the latest by the Flavian period. The lower Deûle valley does not constitute the only cultural « border ». This area of contact, this « culture frontier » is prolonged to the north, along the Lys valley, and to the east, along the Scheldt valley. Does it represent a resistance to Romanization as was occasionally hinted at, or the consequence of the minor strategic and economic interest for Rome of this region in the Higher Empire? The second hypothesis sounds more attractive because everything tends to show that, beside the resources in salt and taxes, echoed in the cadastral surveys, Rome was hardly concerned by this region situated so far apart which could thus, at least for some time (until the 70s) keep its cultural singularities.“
Keywords: Atrebaten; Belgen; Deûletal; Funde; Keramik; Kulturkontakt; Menapier; Nervier; Romanisierung; Römerzeit

Auf dem Weg zur grenzüberschreitenden Metropole? Verflechtungen und Kooperation im belgisch-französischen Städtedreieck Lille-Kortrijk-Tournai - Burdack, Joachim (Europa Regional, 2000)
Inhaltstext: „Die bereits seit langer Zeit "durchlässige" Grenze zwischen Frankreich und Belgien entwickelte sich in den 90er Jahren immer mehr zur "offenen" Grenze. Die Durchlässigkeit betrifft nicht nur die Territorialgrenze, sondern teilweise auch die sogenannten "Systemgrenzen", z. B. den Arbeitsmarkt, Teile des Schulwesens und des privaten Gesundheitswesens. Grenzüberschreitende Aktivitäten der Bevölkerung gehören im Städtedreieck Lille-Kortrijk-Tournai zum Alltag. Vielfalt und Intensität der Aktivitäten bestätigen die These, daß sich ein grenzüberschreitender Aktionsraum im Grenzgebiet herausgebildet hat. Dieser Aktionsraum umfaßt vor allem die unmittelbar an der Grenze gelegenen Gemeinden. Grenzüberschreitende Kooperationen auf lokaler und regionaler Ebene haben dagegen erst in den letzten Jahren ein größere Bedeutung erlangt. In den 90er Jahren ist ein breites Spektrum von Kooperationen auf intraregionaler und kommunaler Ebene entstanden, die einen neuen bottom up-Ansatz der Zusammenarbeit ohne Einbeziehung zentralstaatlicher Institutionen darstellen. Den Hintergrund für das neue Interesse an einer Zusammenarbeit mit den Nachbarstädten jenseits der Grenze bildet das Ziel durch Vernetzung eine "europäische Größenordnung" zu erreichen um sich als Knotenpunkt im entstehenden Netz europäischer Metropolen zu etablieren. Trotz der Vielzahl der grenzüberschreitenden Kooperationen auf verschiedenen Ebenen (Gemeinden, Gemeindeverbände, Regionen) ist das belgisch-französische Städtedreieck ist noch weit davon entfernt eine grenzüberschreitende Metropole zu bilden. Interconnections and cooperation in the French-Belgian city triangle Lille-Kortrijk-Tournai The border between France and Belgium, which has long been regarded as "permeable", developed during the 1990s into more and more of an "open" border. The permeability pertains not only to the territorial border, but in part also to the so-called system borders, e.g. the job market, parts of the school system and the private health system. Border-transcending activities form part of the every-day life of the population in the city triangle Lille-Kortrijk-Tournai. The diversity and intensity of the activities confirm the thesis that a border-transcending activity space has developed in the border region. This action space incorporates primarily the communities in the immediate vicinity of the border. In comparison to this, it is only in recent years that border-transcending cooperations on local and regional levels have gained a greater importance. In the 1990s a wider spectrum of cooperations on the intra-regional and community levels arose, which demonstrate a new bottom-up approach to cooperation without the involvement of centralised state institutions. The background for the new interest in cooperation with neighbouring cities on the other side of the border is the aim to create an entity having a "European order of magnitude" and to establish this as a junction point in the existing network of European metropoles. In spite of the large number of border-transcending cooperations on various levels (communities, community societies, regions), the French-Belgian city triangle is still far from becoming a border-transcending metropolis.“
Keywords: Belgien; Departement Nord; Eurométropole Lille-Kortrijk-Tournai; Frankreich; Grenzgebiet; Grenzüberschreitende Kooperation; Hennegau; Kortrijk; Lille; Metropolisierung; Regionalentwicklung; Stadtentwicklung; Tournai; Westflandern